Experimental Study: Acceptance of Student Moral Developing Through Games Education with Expectation Confirmation Theory - Wibowo, Tony; Lijaputra , Delphy; Marcellino, Marcellino; Syahputra , Bayu (Universitas Medan Area, 2025)
Students' moral development is an important aspect of education, especially in the digital era, where media plays a significant role in the formation of moral values. Video games as interactive media have become a potential tool for developing ethical and moral decision-making abilities. Video games offer a simulated environment that allows students to confront complex moral dilemmas, which have previously been shown to hone critical thinking skills. This study explores the acceptance of video games as a tool for developing students' moral reasoning, using the Expectation Confirmation Theory (ECT), Technology Acceptance Model (TAM), and DeLone and McLean Information System Success Model (D&M). Involving 150 students, the study measured constructs such as perceived usefulness (PU), perceived ease of use (PEOU), information quality (IQ), system quality (SQ), user satisfaction (US), intention to use (IU), and user behavior (UB). Results from SEM analysis showed that while perceived usefulness and ease of use positively influenced intentions to use, actual user behavior did not always align with these intentions after confirmation. However, user satisfaction remained a strong predictor of continued engagement. This emphasize the need for better alignment between user expectations and experiences. These findings highlight the potential of video games in moral education and suggest avenues for improving their design and implementation to enhance educational outcomes